Achieving portable and efficient parallel CORBA objects - Denis, Alexandre; Pérez, Christian; Priol, Thierry (Concurrency and computation, 2003)
With the availability of Computational Grids, new kinds of applications are emerging. They raise the problem of how to program them on such computing systems. In this paper, we advocate a programming model based on a combination of parallel and distributed programming models. Compared to previous approaches, this work aims at bringing single program multiple data (SPMD) programming into CORBA in a portable way. For example, we want to interconnect two parallel codes by CORBA without modifying either CORBA or the parallel communication API. We show that such an approach does not entail any loss of performance compared to previous approaches that required modification to the CORBA standard. Moreover, using an ORB that is able to exploit high‐performance networks, we show that portable parallel CORBA objects can efficiently make use of such networks. Copyright © 2003 John Wiley & Sons, Ltd.